Vision of the upper limb fails to compensate for kinesthetic impairments in subacute stroke. (December 2018) - Semrau, Jennifer A.; Herter, Troy M.; Scott, Stephen H.; Dukelow, Sean P.
Abstract: Kinesthesia is an essential component of proprioception allowing for perception of movement. Due to neural injury, such as stroke, kinesthesia can be significantly impaired. Throughout neurorehabilitation, clinicians may encourage use of vision to guide limb movement to retrain impaired kinesthesia. However, little evidence exists that vision improves kinesthetic performance after stroke. We examined behavioral and neuroanatomical characteristics of kinesthesia post-stroke to determine if these impairments improve with vision. Stroke subjects (N = 281) performed a robotic kinesthetic matching task (KIN) without and with vision at ∼10 days post-stroke. A robotic exoskeleton moved the stroke-affected arm while subjects mirror-matched the movement with the opposite arm. Performance was compared to 160 controls. Spatial and temporal parameters were used to quantify kinesthetic performance. A Kinesthetic Task Score was calculated to determine overall performance on KIN without and with vision. Acute stroke imaging (N = 236) was collected to determine commonalities in lesion characteristics amongst kinesthetic impairment groups. Forty-eight percent (N = 135) of subjects had post-stroke impairment in kinesthesia both without and with vision. Only 19% (N = 52) improved to control-level performance with vision. Of the 48% of subjects that failed to improve with vision, many (N = 77, 57%) had neglect and/or field deficits. Notably 58 subjects (43%) did not have these deficits and still failed to improve with vision. Subjects who failed to improve with vision often had lesions affecting corticospinal tracts, insula, and parietal cortex, specifically the supramarginal gyrus and inferior parietal lobule. Many individuals could not use vision of the limb to correct for impaired kinesthesia after stroke. Subjects that failed to improve kinesthesia with vision had lesions affecting known sensorimotor integration areas. Our results suggest that integration of spatial information is impaired in many individuals post-stroke, particularly after parietal cortex damage. The result is a disconnect between kinesthetic and visuomotor processing necessary for visual limb guidance.